Variabilidade genética e variação de ploidia em espécies de Eriotheca (Bombacoideae Malvaceae) com diferentes sistemas reprodutivos - Marinho, Rafaela Cabral (2013)
Reproduction in plants is predominantly sexually, although asexuality has been documented in many taxa. Apomixis is the focus of this study, defined as the production of seeds without fertilization, in which embryos develop directly from the maternal tissue, and are genetically identical to the mother plant. Polyembryony (formation of more than one embryo per seed) and polyploidy are commonly associated with the Cerrado species that show apomixis. Apomictic taxa show different cytotypes and reproductive mosaics that are good targets for study. Thus, we selected two species of the genus Eriotheca (subfamily Bombacoideae, family Malvaceae) from the Brazilian Cerrado, which have reproductive and cytotypic mosaic. Dominant markers ISSR (Inter Simple Sequence Repeated) were used to evaluate the consequences of apomixis and sexual reproduction on the population s genetic structure. The results showed that apomictic, polyploid and polyembrionic populations have diversity indices very close or even greater than sexual populations. Cytotypes of Eriotheca species were analyzed for morphology pollen grain and stomata as inference of ploidy. These analyses showed that the two structures are efficient to perform this estimate, providing basic procedures for a study in a regional scale. Finally, an analysis of chromosome numbers for some Bombacoideae species and a compilation of chromosome number for species of Malvaceae sl. was carried out to see how these numbers varied in the family. This study demonstrated some new chromosome number and a clear chromosomal evolution, indicating that a whole genome duplication seems to be a feature of the Bombacoideae subfamily, which has chromosome numbers significantly higher than the other subfamilies.